Exploring the barriers and facilitators to the acceptability of donor human milk in eastern Uganda - a qualitative study - Sarah Magowan; Kathy Burgoine; Collin Ogara; James Ditai; Melissa Gladstone (BMC, 2020)
Abstract Background Human milk is the best nutrition for all infants. When the mother's own milk is not available, the World Health Organization recommends the use of donated human milk and milk banking for neonates born prematurely or with medical problems. Donor human milk is rarely available in low-resource settings where both the rates of preterm birth and neonatal mortality are highest. The potential to reduce neonatal mortality through use of donated human milk is one that is yet to be fully explored in the African setting. For the introduction of any new health intervention to be successful, determining the barriers and facilitators to its acceptability is a vital first step. There are limited studies on this in sub-Saharan Africa. Methods This qualitative study used focus group discussions and in-depth interviews to explore the potential barriers and facilitators to utilizing donated human milk for neonates in a hospital setting in eastern Uganda from the perspectives of caregivers (parents, grandparents) and healthcare workers. Results Six focus group discussions involving 28 caregivers were conducted in a hospital setting in eastern Uganda. Four in-depth interviews were then also held with healthcare staff. Lack of knowledge of donated human milk emerged with discussants, and the barriers relating to transmission of infection (HIV) and poor hygiene. Common reasons which facilitated its acceptability were; a general knowledge and recognition that human milk is better than formula milk and a strong belief by caregivers in healthcare workers providing knowledgeable and safe care. Healthcare workers were supportive of introducing donor human milk but perceived a need for community and hospital education programs to enable this to be facilitated and scaled up. Conclusions This study shows that donor human milk can be acceptable to the caregivers of vulnerable babies in hospital settings in Uganda. Lack of awareness of donor human milk, its benefits and the methods of screening, acquisition and storage of donor milk are all barriers that could be addressed through improved education. This study advocates for national policies and programs that build capacity for effective and sustainable donor milk banking.